On determining the hinterlands of China's foreign trade container ports. (May 2020) - Wan, Shulin; Luan, Weixin; Ma, Yu; Haralambides, Hercules
Abstract: The boundary lines of the hinterlands of container ports, for as long as these exist, serve as reference points for future port development and infrastructure planning. In earlier efforts to delineate the hinterlands of Chinese ports, either the number of ports considered was limited, or the demarcation of hinterlands was based on aggregate port throughput only. As a result, none of these studies has allowed a clear understanding of the characteristics of shared hinterlands. To address such shortcomings, the membership degree method and the Huff model have been used here to delineate, if at all possible, the hinterlands of China's 20 major foreign trade container ports. The results reveal the existence of fierce port competition for China's hinterlands, with the hinterland characteristics of different types of ports varying in scope and spatial continuity. Our research has important policy implications for central- and local governments, as well as port authorities. In short, ways to strengthen inter-provincial port cooperation should be a top priority to policymakers going forward. Due to the unavoidable onslaught of diseconomies of scale in cargohandling, international hub ports should focus on the development of strong, port-centric maritime clusters and international shipping centres. Regional hub ports should coordinate better their relationship with international hubs and feeder ports. Finally, the latter ports need to plan their development cautiously in order to avoid unfettered and wasteful expansion. Highlights: The hinterlands of seaports are mainly concentrated within 350 km off the coastline. Hinterlands serving international hubs are segmented and discontinuous. Hinterlands of international hubs, regional hubs, and feeder ports overlap noticeably. Hinterland boundaries targeting specific goods, rather than aggregate port throughput, could better guide port planning.